Long-term results of ab-initio introduction of everolimus after liver transplantation. (March 2023) - Pedini, D.; Angelico, R.; Latini, R.; Quaranta, C.; Materazzo, M.; Toti, L.; Manzia, T.M.; Tisone, G.
Abstract : Introduction: Ab-initio introduction of Everolimus in liver transplantation immunosuppression regimens allows weaning of Calcineurin Inhibitors (CNI) and Mycophenolate levels consequently reducing the common complications associated to their use. Aim: The primary aim of our study was the analysis of graft and recipient survival at the 5- and 10-year follow-up timepoints. The secondary aim was to assess the acute and chronic rejection incidence, renal function, and incidence of complications in our cohort. Materials and Methods Results: Observational retrospective monocentric study analyzing all patients undergoing liver transplantation between September 2009 and March 2020, with a minimum follow-up length of 3 months, in whom Everolimus was introduced on post-operative day 1 along with low-dose CNI and Mycophenolate on a steroid-free protocol. One-hundred and sixty-six patients [135 (81%) males, mean age 58 y.o. (20-72)] were included. The overall graft and recipient survivals were 70% and 60% at the 5- and 10-year timepoint respectively. The incidence of acute rejection was 3%. In all the 17 (10%) patients suffering from hepato-renal syndrome at transplant [mean Serum Creatinine 0, 9 mg/dL (1, 6-3, 49)] we observed normalization of the renal function. De-novo malignancies incidence and HCC recurrence were 14% and 1% respectively. In 37 (22%) patients, we were able to taper CNIs up to a Everolimus monotherapy. Conclusions: Ab-initio introduction of Everolimus in liver transplant immunosuppression schemes is safe and associated to a low incidence of acute and chronic rejection. Also, thanks to the reduction of post-operative complications it allows tapering of other immunosuppressants and complete wean-off in 22% of the patients.